DETERMINAN PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA : PERSPEKTIV RASIO KEUANGAN - Mahameru Rosy Rochmatullah (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
This present paper explores the islamic banks in Indonesia. More detail, This study describe the determinant of islamic banks profitability on the view of financial ratios. Employing a multiple linear of regression, the result reveal that the profitability of islamic banking proxied by return on assets (ROA) is determined by the Capital Adequacy Ratio (CAR) which represents the availability of cash capital (current) to guarantee the return on financing, and Non Performing Financing (NPF) which represents the level of financing risk. Meanwhile, The third-party funds proxied by Financing to Deposit Ratio (FDR) has not been proven to determine the profitability of islamic banks in Indonesia. In the end, this study concluded that the availability of cash capital (current) to guarantee the return of financing, and the level of financing risk is a determinant of the profitability of islamic banks in Indonesia. More detailed explanation can be seen in the discussion section. Key word : Islamic Bank; Profitability, Return on asset (ROA); Capital Adequacy Ratio (CAR); Non Performing Financing (NPF); Financing to Deposit Ratio (FDR)